Study on calculation of transversely isotropic dynamic rock mechanical parameters and conversion model between dynamic parameters and static parameters - Zichao Ma; Nailing Xiu; Haifeng Fu; Bing Hou; Dong Chen; Changming Hou (Unconventional Resources, 2023)
The shale oil reservoirs in the Jimsar Sag are strongly heterogeneous. Therefore, it is of practical significance to relate the dynamic elastic stiffness to the static elastic stiffness under the assumption of transverse isotropy. The acquisition of stiffness parameters depends on lab measurements or Sonic Scanner logging. Aiming at the problem that the lab measurements results are limited and discontinuous, the acquisition of special logging data is difficult in the well site, a method using only the conventional well-log data to predict the dynamic elastic stiffnesses of shale is proposed. Inspired by ultrasonic experimental test method, the study simplified the types of tested waves and complemented missing datas. According to the experimental proof, we concluded that: (1) Under the assumption of transverse isotropy, using simplified Thmosen model and velocity conversion relationship can accurately calculate the P-wave and S-wave velocities in the 45° angle direction. (2) Compared with the conventional isotropic algorithm, specify this algorithm can better reflect real mechanical conditions of the formation, and better characterize the variation of mechanical parameters with depth. (3) Effective conversion models between dynamic elastic modulus and static elastic modulus in vertical and horizontal directions were obtained in some areas of Jimsar.